2013
DOI: 10.1007/978-3-642-39206-1_37
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of Polynomial Calculus: New Separations and Lower Bounds

Abstract: Abstract. During the last decade, an active line of research in proof complexity has been into the space complexity of proofs and how space is related to other measures. By now these aspects of resolution are fairly well understood, but many open problems remain for the related but stronger polynomial calculus (PC/PCR) proof system. For instance, the space complexity of many standard "benchmark formulas" is still open, as well as the relation of space to size and degree in PC/PCR. We prove that if a formula re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…In Filmus et al [2013] we obtained a result analogous to Ben-Sasson and Nordström [2008] that there are formulas of worst-case space complexity that require only constant degree. The question of whether degree lower bounds imply space lower bounds remains open, however, and other results in Filmus et al [2013] can be interpreted as implying that the techniques in Bonacina and Galesi [2013] probably are not sufficient to resolve this question. Unfortunately, as discussed toward the end of this article, we also show that it appears unlikely that this problem can be addressed by methods similar to our proof of the corresponding inequality for resolution.…”
Section: Our Contributionsmentioning
confidence: 83%
See 2 more Smart Citations
“…In Filmus et al [2013] we obtained a result analogous to Ben-Sasson and Nordström [2008] that there are formulas of worst-case space complexity that require only constant degree. The question of whether degree lower bounds imply space lower bounds remains open, however, and other results in Filmus et al [2013] can be interpreted as implying that the techniques in Bonacina and Galesi [2013] probably are not sufficient to resolve this question. Unfortunately, as discussed toward the end of this article, we also show that it appears unlikely that this problem can be addressed by methods similar to our proof of the corresponding inequality for resolution.…”
Section: Our Contributionsmentioning
confidence: 83%
“…Or could perhaps even the stronger claim hold that polynomial calculus space is an upper bound on resolution width? These questions remain wide open, but in the recent paper by Filmus et al [2013] we made some limited progress by showing that if a formula requires large resolution width, then the "XORified version" of the formula requires large polynomial calculus space. We refer to the introductory section of Filmus et al [2013] for a more detailed discussion of these issues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding the relation between space and degree, it is open whether degree is a lower bound for space (which would be the analogue of what holds in resolution), but some limited results in this direction were proven in [21]. The same paper also established that the two measures can be separated in the sense that there are formulas of minimal (i.e., constant) degree complexity requiring maximal (i.e., linear) space.…”
Section: Polynomial Calculusmentioning
confidence: 98%
“…As to size versus space in PC, it is open whether small space complexity implies small size complexity, but [21] showed that small size does not imply small space, just as for resolution. Strong size-space trade-offs have been shown in [7], essentially extending the results for resolution in [6,10] but with slightly weaker parameters.…”
Section: Polynomial Calculusmentioning
confidence: 99%